Analysis of Digital Supply Chain Management in E-procurement Service Usage Using Decision Making Trial Method and Evaluation Laboratory in National Public Procurement Agency - Anggar Jati Saesario; Devi Ajeng Efrilianda (Universitas Negeri Semarang, 2023)
This study aimed to identify the implementation of the digital supply chain and its priority in the National Public Procurement Agency’s e-procurement service. To this end, a quantitative study with Decision-Making Trial and Evaluation Laboratory (DEMATEL) method using Matlab R2105a. DEMATEL result showed that eight criteria in the dispatcher group became the main priority in DSCM implementation in LKPP’s e-procurement process. In comparison, the other eight criteria in the receiver group serve as the advanced criteria in DSCM implementation. The planning criterion was the most prioritized and the most influential DSCM criterion in LKPP’s e-procurement service, which covers the distribution requirement process. The three most important DSCM criteria in LKPP’s e-procurement service were the distribution requirement process, delivery and inspection, and transportation management. The analysis showed that some DSCM criteria in LKPP’s e-procurement had met the DSCM principle. Further studies using other methods like Analytic Hierarchy Process (AHP) and Analytical Network Process (ANP) are needed.